Synthesis and Antibacterial Activity of Oximes, Semicarbazones and Phenylhydrazones - M. Hania, Majed (Asian Journal of Chemistry, 2016)
A series of new oximes, semicarbazones and phenyl hydrazones have been synthesized from o-chloroacetophenone, p-methylacetophenone, and p-methoxybenzaldehyde and their antibacterial activity has been studied against E. coli which gave different results of activity.